1992
DOI: 10.1002/casp.2450020103
|View full text |Cite
|
Sign up to set email alerts
|

Determining the need for community alternatives to prevent unnecessary admissions to an adult inpatient psychiatric unit

Abstract: Admissions to an adult psychiatric inpatient unit were monitored for a period of 4 months in order to determine the necessity for those admissions. Staff considered that 34-58 per cent of admissions would have been unnecessary if appropriate alternatives had been available in the community. The study was repeated using a different methodology and 50 per cent of admissions were then considered unnecessary. As these results are based on post-hoc judgements, made with some knowledge of outcome, the conclusions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It may be that less experienced, non-consultant hospital doctors are more inclined to admit patients to inpatient care, particularly if under pressure from families. Similarly, the absence of data on family care circumstances and on community care facilities 19 is a serious problem, given the importance of both statutory and family support services in keeping people out of hospital.…”
Section: Discussionmentioning
confidence: 98%
“…It may be that less experienced, non-consultant hospital doctors are more inclined to admit patients to inpatient care, particularly if under pressure from families. Similarly, the absence of data on family care circumstances and on community care facilities 19 is a serious problem, given the importance of both statutory and family support services in keeping people out of hospital.…”
Section: Discussionmentioning
confidence: 98%
“…The basic rationale is to provide people who might need psychiatric in-patient services with an alternative community-based response and thereby avoid an inappropriate admission to the DGH acute psychiatric in-patient unit. Evidence that inappropriate psychiatric hospital admissions do occur can be found in a number of publications (Bebbington et al, 1992;Tantam et al, 1992;Whittle, 1992;Audit Commission, 1994; The Sainsbury Centre for Mental Health, 1998). There are also a number of studies which show that a variety of community-based psychiatric services can be an effective alternative to acute hospital-based services (Test & Stein, 1980;Hoult, 1986;Muijen et al, 1992;Merson et al, 1992;Dean et al, 1993;Burns et al, 1993;Audit Commission, 1994;Marks et al, 1994;Minghella et al, 1998).…”
Section: Area Support Bedsmentioning
confidence: 99%
“…Lora, Rivolta, and Lanzara (2003), found that 75% of Italian clients experiencing an acute psychiatric episode reported greater satisfaction with community based peer-run programs, which were associated with more respectful treatment of the client and family. In a convenience sample of 60 inpatient clients in the United Kingdom, Whittle (1992) found that 50% reported greater satisfaction with the consumer-run diversion program than the existing inpatient programs.…”
mentioning
confidence: 97%